Evaluation of growth performance and carcass characteristics in response to oral dosing and daily administration of a yucca-derived sarsaponin to finishing steers - Loe, E.R.; Corrigan, M.E.; Greenquist, M.A.; Depenbusch, Brandon E.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred sixty-eight crossbred, yearling steers (737 lb) were used in a finishing trial comparing a yucca-derived sarsaponin (YUCCA) to a control diet. Finishing diets based on dry-rolled corn were fed for an average of 134 days before slaughter. Animals were randomly assigned to treatments and allotted to 54 pens with seven steers each. On day 0, cattle assigned to YUCCA were orally drenched with 50 mL of SarStart® plus (SarTec Inc., Anoka, MN), and control cattle were orally drenched with an equal volume of water. Steers receiving YUCCA were supplemented with 1 gram per steer daily of a dried yucca extract (SarStart® DSC) for the first 30 days on feed, and then with 0.5 gram per steer daily from day 31 to harvest. Body weight, dry matter intake, average daily gain, and feed efficiency were not different between treatments for either the first 30 days or for the entire finishing period. Dressing percentage, hot carcass weight, USDA quality grade, USDA yield grade, and percentage of liver abscesses also were not different between treatments. Incorporating yucca-derived sarsaponin in the ration and as an oral drench had no effect on animal performance or carcass characteristics.
Keywords: Beef; Growth performance; Carcass characteristics; Yucca-derived sarsaponin; Finishing steers